THE CONTESTED AUTHORITIES: Institution and Agency in the Enforcement of Sharia Law in Aceh, Indonesia - Sehat Ihsan Shadiqin; Eka Srimulyani (UIN Sumatera Utara, 2021)
Abstract: This article is aimed to explore the contested authorities in the enforcement of sharia law in Aceh. The existence of these contesting authorities could be observed in the qanun shari’a (the shari’a bylaws) formulation and implementation processes. In Aceh Province, this contestation is also further complicated by a wider contestation among formal and non-formal actors, representing pluralities of Aceh jurisprudence perspectives. Hence, the dynamic of sharia law products and its implementation in Aceh actually [re]presents a unique situation of how pluralities of actors could influence the Sharia Law formulation and its enforcement, and this is also mediated by the historical, political and cultural contexts. This research utilizes a qualitative approach, through a library research data collection which is also combined by few interviews. Generally, it seems that the authorities or agencies of both formal and non-formal institutions sometimes intersect, overlap and contest, which also complicate the production or of the incorporation of moderate Islamic thought. Keywords: religious authority, institution, agency, Islam in Aceh, shariah law